2015
DOI: 10.1093/carcin/bgv124
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-mediated degradation of nuclear envelope proteins during oncogene-induced senescence

Abstract: Cellular senescence is a largely irreversible form of cell cycle arrest triggered by various types of damage and stress, including oncogene expression (termed oncogene-induced senescence or OIS). We and others have previously demonstrated that OIS occurs in human benign lesions, acting as a potent tumor suppressor mechanism. Numerous phenotypic changes occur during OIS, both in the cytoplasm and in the nucleus. These include the activation of autophagy, a catabolic process operating in the cytoplasm and downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…Multiple studies show a close association between the nuclear and sequestering membrane. 26,27,32,46,47 Together, these data indicate that the nuclear membrane may contribute to the autophagosomal membrane in addition to being an autophagic target. Future studies will characterize the molecular features of the nuclear autophagosomal membrane and the underlying molecular mechanisms that drive autophagic targeting of the nuclear membrane.…”
Section: Roles Of Nuclear Membrane In Nuclear Autophagymentioning
confidence: 79%
See 1 more Smart Citation
“…Multiple studies show a close association between the nuclear and sequestering membrane. 26,27,32,46,47 Together, these data indicate that the nuclear membrane may contribute to the autophagosomal membrane in addition to being an autophagic target. Future studies will characterize the molecular features of the nuclear autophagosomal membrane and the underlying molecular mechanisms that drive autophagic targeting of the nuclear membrane.…”
Section: Roles Of Nuclear Membrane In Nuclear Autophagymentioning
confidence: 79%
“…28 Recent studies have highlighted the importance of nuclear autophagy in physiological and pathological processes such as cancer. [29][30][31][32][33][34] Nevertheless, the underlying molecular mechanisms remain to be explored.…”
Section: Nuclear Autophagy Is Evolutionarily Conserved In Eukaryotesmentioning
confidence: 99%
“…These findings are consistent with other reports showing that autophagy can trigger pro-senescent events when activated in response to cellular stress. 15,19,21,29 Constitutive baseline autophagy, on the other hand, seems to act usually in a senescence preventing manner playing a crucial role in healthy aging and life span extension. 23,30 In our previous work we have shown a rapid development of senescence in PTEC not only after g-irradiation but also under baseline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…14 Based on the finding that stress-induced autophagy is often followed by the occurrence of senescent cells it was concluded that autophagy might act as a pro-senescent trigger. [15][16][17][18][19] Along these lines, Young et al first proposed autophagy as an effector mechanism for establishment of oncogenic senescence. 17 Autophagy was later also found to contribute to senescence of bile duct epithelial cells and progression toward primary biliary cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Another chromatin component, the linker histone H1, is also depleted in senescent cells [39]. In addition to histone depletion, a recent line of evidence points to a role for autophagy , a protein recycling mechanism, in the degradation of chromatin fragments in the cytoplasm in both RS and OIS [40], and of proteins associated with the nuclear lamina in OIS, including LMNB1 and LMNA [41, 42]. However, it is not completely clear whether H1 depletion is a consequence of the ejection of chromatin into the cytoplasm also known as cytoplasmic chromatin fragments), a decrease in histone synthesis, or other mechanisms [40, 43, 44].…”
Section: Senescent Cells Display Extensive Changes In Chromatin Strucmentioning
confidence: 99%